MADS-box genes and crop domestication: the jack of all traits. (21st February 2018) - Schilling, Susanne; Pan, Sirui; Kennedy, Alice; Melzer, Rainer
Abstract : MADS-box genes are major domestication genes involved in a plethora of developmental processes. They might be ideally suited for future targeted breeding efforts. Abstract: MADS-box genes are key regulators of virtually every aspect of plant reproductive development. They play especially prominent roles in flowering time control, inflorescence architecture, floral organ identity determination, and seed development. The developmental and evolutionary importance of MADS-box genes is widely acknowledged. However, their role during flowering plant domestication is less well recognized. Here, we provide an overview illustrating that MADS-box genes have been important targets of selection during crop domestication and improvement. Numerous examples from a diversity of crop plants show that various developmental processes have been shaped by allelic variations in MADS-box genes. We propose that new genomic and genome editing resources provide an excellent starting point for further harnessing the potential of MADS-box genes to improve a variety of reproductive traits in crops. We also suggest that the biophysics of MADS-domain protein–protein and protein–DNA interactions, which is becoming increasingly well characterized, makes them especially suited to exploit coding sequence variations for targeted breeding approaches.